Inhalation therapy with magnesium sulfate and salbutamol sulfate in bronchial asthma - Meral, Adalet; Çoker, Mahmut; Tanaç, Remziye (The Turkish Journal of Pediatrics, 1996)
Inhalation therapy with magnesium sulfate and salbutamol sulfate was applied to two groups, each consisting of 20 patients with acute asthma. The effects of inhaled magnesium sulfate and salbutamol sulfate were compared. The evaluation of patients was done using respiratory score, peak expiratory flow rate with a Wright peak flow meter, respiration rate, heart rate and blood pressure. Although magnesium sulfate's bronchodilating effect continued for approximately one hour, treatment of acute asthma using salbutamol sulfate inhalation was found to be more successful and its effect continued for six hours.
Keywords: childhood asthma; magnesium sulfate; inhalation therapy